How Will Changes in Globalization Impact Growth in South Asia? - Ghani, Ejaz; Anand, Rahul (2012)
The current global crisis may change globalization itself, as both developed and developing countries adjust to global imbalances that contributed to the crisis. Will these changes help or hinder economic recovery and growth in South Asia? This is the focus of this paper. The three models of globalization--trade, capital, and economic management--may not be the same in the future. Changes in globalization could change the composition of trade flows, capital flows, and economic management, which in turn, could accelerate or restrain growth. South Asia is somewhat peculiar and different from other regions in how it has globalized, although there is a lot of diversity within the region. Its trade characteristics are different. India's growth has been spearheaded by exports of modern services and less by goods exports. Modern service trade tends to be more resilient compared with goods trade. Globalization of services is still at an early stage. So, as consumers pull back in the United States, service trade is likely to be less impacted compared to goods trade. Trade also contributes to growth through knowledge spillovers, externalities, and learning. The global crisis has not reduced the stock of global knowledge. Changes in capital flows are also not likely to have a big impact on growth in South Asia, as South Asia's investments are largely driven by domestic savings. Its dependence on foreign capital is low. South Asia has attracted capital flows that are less volatile. Remittances, which are more resilient, have been the dominant form of capital inflows, exceeding foreign direct investment and other inflows.This global downturn calls for counter-cyclical economic management. But South Asia has limited room for fiscal stimulus, given high debt-to-gross domestic product ratios. Nevertheless, reduced commodity prices have created some fiscal space that can be used for growth enabling infrastructure and safety nets. As South Asia undergoes structural transformation, the region is well positioned to bounce back with global economic recovery.